PREVALENCE OF NURSING DIAGNOSIS IMBALANCED NUTRITION IN HYPERTENSIVE PATIENTS - Marília Araripe Ferreira; Annah Maria Couto Bezerra Carneiro; Mayenne Myrcea Quintino Pereira Valente; Virna Ribeiro Feitosa Cestari; Maria Albertina Rocha Diógenes; Léa Maria Moura Barroso Diógenes (Universidade Federal do Paraná, 2016)
The present study aimed to investigate the prevalence of Nursing Diagnosis Imbalanced Nutrition: more than bodyrequirements in hypertensive patients. Exploratory, descriptive study,with a quantitative approach, with 90 hypertensive patientsmonitored in a secondary care unit. Data collection was performed in 2015 through the administration of a questionnaire onsociodemographic, anthropometric and clinical characteristics of the patients. Categorical variables were summarized by descriptive statistics of frequencies (absolute and relative). Associations between major defining characteristics and diagnosis of imbalanced nutrition wereassessed by Pearson's chi-square test. The referred diagnosis was observed in 82 (91.1%) of the participants, since they presented at least one of the two major defining characteristics: "tricepsskinfold thickness" (p<0.001)or "overweight(20% over their ideal weight)"(p<0.001). The role of nurses in the promotion of strategies aimed to introduce changes in nutritional behavior and the practice of physical activity, contributing to reducing the rates of the referred nursing diagnosis, was demonstrated.